English as a Neutral Language in the Colombian National Standards: A Constituent of Dominance in English Language Education - Carmen Helena Guerrero Nieto; Álvaro Hernán Quintero Polo (Profile: Issues in Teachers' Professional Development)
This article attempts to problematize the way the English language is used in official documents. We will focus on the "Estándares Básicos de Competencias en Lenguas Extranjeras: Inglés" (Basic Standards of Competences in Foreign Languages: English), a handbook issued by the Colombian Ministry of Education. We deem it as a vehicle used to spread a hegemonic and ideological influence and to alienate teachers' beliefs and practices within English language education. To be concise, here we discuss only neutrality as one broad category that emerges in our close examination of how the English language is constructed within the handbook. In this paper, we construct our main points around three forms of neutrality: prescription, denotation, and uniformity.